ERBANDINGAN UNSUR INTRINSIK DALAM CERITA RAKYAT“PUTRI JUNJUNG BUYAH” DI KALIMANTAN TIMUR DAN “PUTRI JUNJUNG BUIH” DI KALIMANTAN SELATAN: SEBUAH KAJIAN INTERTEKSTUAL - Derri Ris Riana (Balai Bahasa Sulawesi Tengah, 2016)
Intertextual research is used to see the relationship between two texts, especially the literature that comes fromdifferent background of social and culture, but they have the same theme. However, intertextual research aboutKalimantan’s folklore has not been done yet. Therefore, by using analysis descriptive method and intertextualapproach, this article wants to explore the folklore of “Putri Junjung Buyah” in East Kalimantan and “PutriJunjung Buih” in South Kalimantan, reveal intertextual relationship, and explain article hypogram and thetransformation between these folklore. The result shows that there is a relationship between “Putri JunjungBuyah” and “Putri Junjung Buih”. This relationship exists on the story background, the appearance of a princess,the struggle of getting something, and the marriage. As article hypogram, “Putri Junjung Buih” is regarded as areference to the next folklore, “Putri Junjung Buyah”. “Putri Junjung Buyah” has been transformated in manyways, especially instrinsic elements, that are story background (setting, social, and culture) and the theme.